Fatores associados ao Acidente Vascular Cerebral Isquêmico na Cardiopatia Reumática Crônica - Marcelle Cristina da Silva Bastos Vasconcelos (2020)
Background: Stroke is a severe complication of rheumatic heart disease (RHD), which may result in major clinical disability and death. Despite significant morbidity and mortality resulting from stroke, limited information is available on stroke in the context of RHD. The aim of the present study was to identify the prevalence and factors associated with ischemic stroke in a large population of patients with RHD. In addition, the predictors of stroke on follow-up were assessed in these patients. Methods: A total of 515 RHD patients was enrolled between September 2010 and August 2019. We conducted a structured clinical and neurological assessment determining the causes and classification of stroke according to Causative Classification System, Oxfordshire Classification and Rankin Scale. We also performed standard echocardiographic evaluation to investigate possible substrate of cardioembolic events. Patients were followed for 3.8 years (ranged from 1 month to 8.6 years), and the occurrence of ischemic stroke was the outcome evaluated during follow-up. Patients who died or underwent valve intervention were censored at the time of the event. Results: The mean age was 46 ± 12 years, with a predominance of women (85%). The most frequent valve lesion was mixed mitral lesion (80%). At the time of enrollment into the study, ischemic stroke was diagnosed in 92 patients (18%), with anterior circulation infarction being the most frequent topography (72%). The factors associated with prior ischemic stroke were atrial fibrillation (AF) (adjusted Odds ratio [OR] 7.239, Confidence Interval [CI] 95% 02.899- 17.525) and transvalvular mean gradient (adjusted OR 0.926, 95% CI 0.870-0.985). There was an interaction between the presence of AF and use of anticoagulants. During the follow-up period, 23 patients (4.5%) had ischemic stroke with an overall incidence of 1.3 events / 100 patients-year. Independent predictors of ischemic stroke during follow-up were prior stroke (adjusted Hazard ratio [HR] 5.113, 95% CI 2.101-12.445) and age (adjusted HR 1.054, 95% CI 1.018-1.093). Others adverse events occurred in 139 patients, including 34 deaths and 105 valve interventions. Conclusions: AF was an important factor associated with stroke even after adjustment for anticoagulation. Prior stroke and age were predictors of stroke on follow-up in this population.